Peak and Plateau Communication Experiences (PCEs): An International Call for Inquiry - Ronald D., Gordon (KOME, 2023)
Maslow’s landmark conception of the generalised “peak experience” is revisited. Next the concept of “peak” communication experiences (PCEs), originally derived four decades ago from the generalised Maslow model, is reviewed. PCEs are defined as our times of highest happiness and fulfilment arising from our communication with others. While “peak” communication experiences have received scant conceptual and empirical attention, the work that has been done is briefly surveyed. The under-told story of Maslow’s significant end-of-life conceptualising of “plateau” experiencing is then highlighted, and it is recommended that “plateau” communication experiences be included within the upper-distribution PCE domain going forward. The development of a “positive communication” paradigm within the communication discipline is traced, and it is suggested there now exists a foundational knowledge structure to provide conceptual home for inquiry into PCEs. Lastly, suggestions for the exploration of both “plateau” and “peak” communication experiences (PCEs) are offered.